THE INFLUENCE OF SURFACE WIND ON THE SALINITY DISTRIBUTION AND CIRCULATION IN THE COASTAL WATERS OF THE RED RIVER DELTA, VIETNAM - Vinh, Vu Duy; Baetens, Katrijn; Luyten, Patrick; Tu, Tran Anh; Anh, Nguyen Thi Kim (Vietnam Journal of Marine Science and Technology, 2014)
A sufficiently well validated hydro-physics model for the coastal zone of the Red River delta area in Vietnam was presented. The development code was COHERENS V2.0, a three-dimensional hydrodynamic multi-purpose model for coastal and shelf seas based on the finite element method. The results of the model with 10 scenarios simulations show the role of wind condition combined with tidal oscillation and river discharge on salinity distri-bution and circulation of the red river coastal area. Wind NE in the dry season make increasing velocity of residual current, intensify salinity in the coastal zone and gradient of salinity on the vertical. On the other hand, wind SE in the rainy season makes intensify fresh water to seaward, increasing range of river water on the surface and seawater on the bottom in the coastal zone.